Numerical study on crack propagation in linear elastic multiphase composite materials using phase field method. Issue 1 (3rd December 2018) - Li, Xiang; Chu, Dongyang; Gao, Yue; Liu, Zhanli
Abstract : Purpose: The purpose of this paper is to develop an efficient numerical method to study the complex crack initiation and propagation in linear elastic multiphase composites. Design/methodology/approach: A phase field method is developed to study the complex fracture behavior in multiphase composites. A damage threshold is introduced for referring crack initiation in the proposed method. The damage threshold is assigned as a material property so that different composite components possess different thresholds. In this manner, smooth transition from crack initiation to propagation is revealed. Findings: The proposed method is used to investigate complex crack evolution in mesoscale cementitious composite, which consists of aggregates, matrix and void pores. From a mesoscale point of view, it is found that cracks prefer to evolve within the matrix phase. As a crack encounters an aggregate, it tends to bypass the aggregate and evolve along the interface. Cracks tend to avoid to penetrate through aggregates. Also, cracks tend to be attracted by void pores. From a mesoscale point of view, it is revealed that the elastic modulus and strength of concrete models are closely related to porosity. Originality/value: A criterion with a damage threshold is introduced to the proposed method. The criterions with and without a damage threshold are compared with each other in details. The proposed method is proven to be a useful tool to study mechanical behavior and crack evolution of brittle multiphase composites.